Política de habitação x déficit habitacional: como anda a despesa pública em habitação de interesse social em Belém do Pará? - PINTO, Rondinelly Nascimento (2024)
This article aims to demonstrate the increase in the allocation and disbursement of financial resources aimed at financing social housing in Belém (PA). To this end, an analysis was carried out on the foundations of the right to housing at the constitutional level, as well as at the international level, in order to identify the housing deficit, in the period from 2018 to 2022, in the municipality of Belém (PA), taking into account the current unfavorable scenario for the low-income population. This is a research with a qualiquantitative approach of an exploratory, bibliographic and documentary nature, which occurred through the collection of budgetary-financial planning standards for the municipality of Belém do Pará, contained in the Pluriannual Plan, the Budgetary Guidelines Law and the Law Annual Budget, as well as the selection of doctrinal references regarding the right to housing in Brazil, in addition to the extraction of data relating to budgetary authorizations/allocations, in the financial years from 2018 to 2022, intended for the public policy on Social Interest Housing. The result of the research reveals that, during the period studied, there was a shortening of the target for reducing the housing deficit, as well as a shrinking of financial resources for investment in housing policy in the researched municipality, in addition to the delivery of only 53.47% of the housing units planned for the period researched. Finally, it was identified during the research that the Municipal Housing Department does not develop an effective control system over the quantity of housing under construction, built and not delivered and built and delivered, so that the public authorities can optimize the quality of its internal controls and increase the quality of information transparency.